Unique Nitrogen-Doped Carbon Polyhedron Embedded with Co Derived Core-Shell Nanoparticles for the Electro-Catalysis towards Hydrogen Peroxide Redox Reaction and Nonenzymatic Detection. Issue 3 (1st March 2021) - Li, Qiuxia; Mo, Guangquan; Ye, Guodong
Abstract : Unique nitrogen-doped carbon polyhedron embedded with core–shell Co@Co3 O4 nanoparticles (Co@Co3 O4 -NC) was synthesized with the pyrolysis of zeolitic imidazolate framework. Novel two-step redox pyrolysis with accurate control of ZIF-67 carbonization and Co ion transformation during pyrolysis was applied. Co@Co3 O4 -NC was characterized by field emission scanning electron microscope, high-resolution transmission electron microscope, powder X-ray diffraction, X-ray photoelectron spectroscopy and nitrogen adsorption-desorption experiment. Co@Co3 O4 -NC displayed a strong electrochemical catalysis towards both H2 O2 oxidation and H2 O2 reduction. By using Co@Co3 O4 -NC prepared sensor, efficient detection of H2 O2 was achieved not only by the H2 O2 oxidation at a positive potential but also by the H2 O2 reduction at a negative potential. At 0.30 V, the resulting sensor exhibited a rapid amperometric response (2 s), low detection limit (0.056 μ M) and broad detection linear range (0.1 μ M–40.0 mM). Besides, at −0.30 V, the resulting sensor also exhibited a rapid amperometric response (4 s), low detection limit (0.96 μ M) and broad detection linear range (2.0 μ M–60.0 mM). Additionally, Co@Co3 O4 -NC prepared sensor also presented a notable selectivity, high reproducibility and long-term stability. Our results proved that Co@Co3 O4 -NC was an efficient electro-catalyst for H2 O2 redox reaction, and Co@Co3 O4 -NC prepared sensor could be a promising sensing platform for the nonenzymatic detection of H2 O2 .